2014
DOI: 10.1007/s10546-014-9922-6
|View full text |Cite
|
Sign up to set email alerts
|

Extension of the Averaging Time in Eddy-Covariance Measurements and Its Effect on the Energy Balance Closure

Abstract: The modified ogive analysis and the block ensemble average were employed to investigate the impact of the averaging time extension on the energy balance closure over six land-use types. The modified ogive analysis, which requires a steady-state condition, can extend the averaging time up to a few hours and suggests that an averaging time of 30 min is still overall sufficient for eddy-covariance measurements over low vegetation. The block ensemble average, which does not require a steady-state condition, can ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
126
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(138 citation statements)
references
References 51 publications
8
126
0
Order By: Relevance
“…The EBCs of the present study agree with those of other studies performed over agricultural land, where EBCs are typically characterized by high energy residuals (20-40%) (Charuchittipan et al, 2014;Foken, 2008a;Panin and Bernhofer, 2008;Stoy et al, 2013). The random errors of our EC fluxes are also in a good agreement with random errors reported by Mauder et al (2013) and Foken (2008a).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The EBCs of the present study agree with those of other studies performed over agricultural land, where EBCs are typically characterized by high energy residuals (20-40%) (Charuchittipan et al, 2014;Foken, 2008a;Panin and Bernhofer, 2008;Stoy et al, 2013). The random errors of our EC fluxes are also in a good agreement with random errors reported by Mauder et al (2013) and Foken (2008a).…”
Section: Discussionsupporting
confidence: 92%
“…Low EBCs (60-80 %) were mainly observed at various agricultural sites and bare soil, whereas over forest they were typically higher (80-90 %) (Charuchittipan et al, 2014;Wilson et al, 2002;Foken, 2008a;Panin and Bernhofer, 2008;Stoy et al, 2013). The imbalance usually occurs during day time, particularly around noon, whereas during the night when fluxes are low EBC is often close to unity (Oncley et al, 2007).…”
Section: K Imukova Et Al: Energy Balance Closure On a Winter Wheat mentioning
confidence: 96%
“…The imbalance in Equation (1), often found when Q H and Q E are obtained from the measurement by the EC technique [31][32][33], can be significantly compensated with the contribution from secondary circulations which can hardly be measured by the EC system [31,34]. This study followed the energy balance closure (EBC) correction suggested by Charuchittipan et al [34]: where Res is the residue energy flux, c p is the specific heat of air, λ is the heat of evaporation for water, and superscripts indicate the measurement or correction methods. Bo EBC-HB is the corrected Bowen ratio, which should be either calculated iteratively until it converges [34] or calculated by solving Equation (2), which results in the analytic solution:…”
Section: Correction For Energy Balance Closurementioning
confidence: 99%
“…This study followed the energy balance closure (EBC) correction suggested by Charuchittipan et al [34]: where Res is the residue energy flux, c p is the specific heat of air, λ is the heat of evaporation for water, and superscripts indicate the measurement or correction methods. Bo EBC-HB is the corrected Bowen ratio, which should be either calculated iteratively until it converges [34] or calculated by solving Equation (2), which results in the analytic solution:…”
Section: Correction For Energy Balance Closurementioning
confidence: 99%
“…The authors argue that stationarity can be still assumed, because for the investigated 16-day time series the diurnal cycle was similar each day, and the trend of adjacent averages, which is the crucial stationarity criterion for the EC method, was smaller for 24 h values than for 30 min values. The finding that at some sites the energy residual may consist to a large extent of sensible heat was recently supported by an in-depth evaluation of additional EC flux data of the LITFASS-2003 experiment acquired over six different land use types (Charuchittipan et al, 2014).…”
Section: Introductionmentioning
confidence: 84%